Cortical blindness as severe neuro-ophthalmological manifestation of tuberous sclerosis complex - Ortiz Z., Alvaro I. (GMS Ophthalmol Cases, 2017)
Patients with retinal lesions related to tuberous sclerous complex (TSC) commonly have no impairment of visual acuity. We present a case of a 1-year-old Hispanic girl with TSC in which bilateral cortical blindness is documented.